Analysis of the prevalence and sensitivity to antimycotic drugs of C. albicans strains in Bukovina during 2019–2023 - O. O. Blinder; O. V. Blinder; A. V. Humenna; S. Ye. Deineka; A. O. Mikhieiev (Zaporožskij Medicinskij Žurnal)
The aim of this work was to study the prevalence of C. albicans strains among patients with inflammatory processes of various localization during 2019–2023 years and to analyze dynamics in the sensitivity of these isolates to antifungal drugs.